2023
DOI: 10.1088/1755-1315/1136/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of model-based techniques for pipe burst location in water distribution networks

Abstract: The current paper compares the performance of three model-based techniques for the automatic location of pipe burst events in water distribution networks. The first technique is based on nodal pressure sensitivities, the second solves an inverse analysis problem and the third technique uses hydraulic simulation to train a classifier. A real case study is used and a set of artificial measurements is generated for a number of pipe burst scenarios, with fixed burst location and variable pressure and flowrate nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…As such, when the uncertainty is significant, those methods can pinpoint to completely wrong locations. Ferreira et al [ 34 ] compared three distinct model-based techniques for this same case study and concluded that given high uncertainty levels (e.g., noise level of 3%), the unique inferred location is often quite distant from the true location (e.g., between 200 and 300 m). This unique location is not an ideal result since, if wrongly inferred, the water utility may be looking for a pipe burst where there is not one.…”
Section: Application: Results and Discussionmentioning
confidence: 99%
“…As such, when the uncertainty is significant, those methods can pinpoint to completely wrong locations. Ferreira et al [ 34 ] compared three distinct model-based techniques for this same case study and concluded that given high uncertainty levels (e.g., noise level of 3%), the unique inferred location is often quite distant from the true location (e.g., between 200 and 300 m). This unique location is not an ideal result since, if wrongly inferred, the water utility may be looking for a pipe burst where there is not one.…”
Section: Application: Results and Discussionmentioning
confidence: 99%
“…The identification of such critical areas can be carried out by simulating a pipe burst event (i.e., using the hydraulic simulation model) in distinct network locations and by attempting to locate such simulated bursts in the network using a given advanced algorithm, for instance, inverse analysis, sensitivity-based methods, or classifier-based methods [29]. If the simulated event is correctly located, it means that a real event occurring in such a location can also be potentially located.…”
Section: Identification Of Critical Areas For Pipe Burst Locationmentioning
confidence: 99%
“…The pressure measurements generated by such a simulated event are then used by the advanced algorithm to locate such an event. The implemented advanced algorithm is based on a pattern recognition classifier (further details are presented in [29]), but distinct methods could be used (e.g., inverse analysis). The assessment of the correct burst location is given by the distance between the identified location and the correct location, measured along the network pipes (the shortest distance) or given by the Euclidean distance.…”
Section: Identification Of Critical Areas For Pipe Burst Locationmentioning
confidence: 99%